Comparative Determinants of Quality of Growth in Developing Countries - Simplice Asongu; Ndemaze Asongu (African Governance and Development Institute (AGDI), 2017)
This study explores a new dataset in order to present the comparative determinants of growth quality in 93 developing countries for the period 1990-2011. We employ both cross-sectional and panel estimation techniques with contemporary and non-contemporary specifications. The determinants are quite heterogeneous in significance and magnitude with substantial inclinations to specifications and estimation techniques. We present and discuss the findings in increasing magnitude of significance so as to ease comparative readability. We also discuss how specificities in the modelling techniques are relevant for targeting growth quality. The results are timely and relevant for the post-2015 inclusive and sustainable development agenda.
Keywords: O40; O57; I10; I20; I32; 330; Quality of growth; Development